AIR POLLUTION EXPOSURE AND NEURODEGENERATIVE DISEASE PROGRESSION IN POST-OPERATIVE PATIENTS: A META-ANALYSIS - Muhammad Haider; Maryum Tayyab; Hamza Saeed; Maham Mujeeb; Hamza Mahmood (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: This meta-analysis examines the impact of air pollution on the progression of neurodegenerative diseases in post-operative patients. By synthesizing data from global studies, it highlights the contributions of nitrogen dioxide (NO₂), particulate matter (PM2.5 and PM10), and other pollutants to cognitive decline and disease aggravation. Methods: Data were synthesized from a comprehensive review of global studies published between 2000 and 2023, focusing on the effects of pollutants such as nitrogen dioxide (NO₂), particulate matter (PM2.5 and PM10), and sulfur dioxide (SO₂). Results: The findings indicate a robust correlation between prolonged exposure to air pollutants and an accelerated rate of cognitive decline and disease progression. Specifically, long-term exposure to PM2.5 and NO₂ was associated with increased neuroinflammation, oxidative stress, and compromised blood-brain barrier integrity. Conclusion: These results highlight the urgent need for strict environmental regulations and targeted public health initiatives aimed at reducing air pollution levels.